Sealing sheet

By designing a sealing sheet with a two-layer structure, using the combination of thermosetting resin and thermoplastic resin, the buried property and pollution problems of the resin sheet during sealing are solved, and the heat resistance and reliability after sealing is improved, achieving high efficiency sealing effect.

CN111716847BActive Publication Date: 2024-12-13NITTO DENKO CORP
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202010194901.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-03-19
Filing Date
2020-03-19
Publication Date
2024-12-13
Estimated Expiration
2040-03-19

AI Technical Summary

Technical Problem

When the existing sealing sheet is heated and pressed, it is difficult for the resin sheet to penetrate smoothly between the electronic components, resulting in a decrease in buried property and may contaminate the substrate, and the heat resistance after sealing is insufficient.

Method used

A sealing sheet is designed, which consists of two layers of structures: a contact layer and an exposed layer, which consists of a thermosetting resin containing epoxy resin and a phenolic resin, and the exposed layer is composed of acrylic resin and a silica filler material. The composition, thickness ratio meets specific conditions at 90°C, ensures flexibility and depression, achieves good buriedness and low pollution, and improves heat resistance and reliability after thermal curing.

Benefits of technology

High buried properties and low pollution during sealing are achieved, the heat resistance and reliability of the sealed electronic component packaging is ensured, unnecessary gaps and contamination are avoided, and cracks are reduced during thermal cycles.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN111716847B_ABST
    Figure CN111716847B_ABST
Patent Text Reader

Abstract

A sealing sheet having good embedding property and low contamination property during sealing, and good heat-resistant reliability after sealing is provided. The sealing sheet (1) is a sealing sheet for sealing an electronic component (51), wherein the sealing sheet comprises, in order toward the upper side: a first layer (2) in contact with the electronic component (51) when the electronic component (51) is sealed, and a second layer (3) exposed to the outside, wherein the first layer (2) and the second layer (3) are each thermosetting, the upper surface of the second layer (3) is softer than the lower surface of the first layer (2) at 90°C, and the ratio of the thickness T2 of the second layer (3) to the thickness T1 of the first layer (2) satisfies the following formula 1.5: <T2 / T1<5。
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a sealing sheet, and more particularly to a sealing sheet for sealing electronic components. Background Art

[0002] Conventionally, it is known to obtain an electronic component package by sealing an electronic component mounted on a substrate with a sealing sheet.

[0003] As such a sealing sheet, for example, a resin sheet having an outermost layer and an innermost layer, wherein the outermost layer contains a thermosetting resin and an inorganic filler has been proposed (for example, refer to Patent Document 1).

[0004] Prior art literature

[0005] Patent Literature

[0006] Patent Document 1: Japanese Patent Application Publication No. 2018-103584 Summary of the invention

[0007] Problem that the invention aims to solve

[0008] In addition, when the resin sheet is heated and pressed to seal the electronic components, from the perspective of manufacturing efficiency, multiple electronic components mounted on a large substrate are prepared, and the multiple electronic components are sealed together with a sealing sheet, and then monolithic. However, sometimes the resin sheet does not smoothly penetrate between the adjacent multiple electronic components, and the embedding property of the resin sheet is reduced. In this case, an unnecessary gap (air) is generated inside the obtained electronic component package, specifically between the substrate and the resin sheet.

[0009] On the other hand, if the fluidity of the resin sheet is increased to improve embedding properties, the following disadvantages may occur: the resin sheet flows greatly and wets and spreads on the substrate, and the resin sheet protrudes outside the substrate. In this case, the surroundings of the substrate (for example, a pressing device, etc.) will be contaminated by the resin sheet.

[0010] Furthermore, the sealed electronic component package is also required to have heat-resistant reliability such as no cracking due to thermal cycles.

[0011] The present invention provides a sealing sheet having excellent embedding property and low contamination property during sealing and excellent heat-resistant reliability after sealing.

[0012] Solutions for solving problems

[0013] The present invention [1] includes a sealing sheet for sealing an electronic component, wherein the sealing sheet comprises, in order toward one side in the thickness direction: a first layer in contact with the electronic component when the electronic component is sealed, and a second layer exposed to the outside, wherein the first layer and the second layer are each thermosetting, and one surface of the second layer in the thickness direction is softer than the other surface of the first layer in the thickness direction at 90° C., and the ratio of the thickness T2 of the second layer to the thickness T1 of the first layer satisfies the formula 1.5 <T2 / T1<5。

[0014] The present invention [2] comprises the sealing sheet described in [1], wherein the ratio of the depression amount D2 of one surface of the second layer in the thickness direction in an iron ball drop test at 90°C to the thickness T2 of the second layer satisfies the formula 0.1 <D2 / T2<0.2。

[0015] Effects of the Invention

[0016] According to the sealing sheet of the present invention, one surface of the second layer in the thickness direction is softer than the other surface of the first layer in the thickness direction at 90°C, and the ratio of the thickness T2 of the second layer to the thickness T1 of the first layer satisfies the prescribed conditions, so that the embedding property and low contamination property during sealing and the heat-resistant reliability after sealing are good. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 middle, Figure 1 A and Figure 1 B shows a diagram for explaining one embodiment of the sealing sheet of the present invention and its production, Figure 1 A shows a cross-sectional view of the sealing sheet, Figure 1 B shows a diagram of preparing the first layer and the second layer respectively.

[0018] Figure 2 middle, Figure 2 AB shows a diagram for explaining a method for measuring the amount of depression in an iron ball drop test. Figure 2 A shows a diagram of preparing a sealing sheet and an iron ball, Figure 2 B shows the amount of depression and its enlarged view.

[0019] Figure 3 middle, Figure 3 AC for use Figure 1 A is a diagram showing a method of sealing an electronic component using a sealing sheet, Figure 3 A shows a diagram of preparing an electronic component mounting substrate and a sealing sheet, respectively. Figure 3 B shows a diagram of sealing an electronic component with a sealing sheet and thermally curing the sealing sheet, Figure 3 FIG. C shows a diagram of a plurality of electronic component packages obtained.

[0020] Figure 4 A plan view is shown when evaluating contamination properties in Examples.

[0021] Description of Reference Numerals

[0022] 1 Sealing sheet

[0023] 2 Layer 1

[0024] 3 Layer 2

[0025] 8 Sealing sheet

[0026] 50 substrates

[0027] 51 Electronic components DETAILED DESCRIPTION

[0028] exist Figure 1 AB and Figure 3 In C, the up-down direction on the paper is the up-down direction (thickness direction). The upper side on the paper is the upper side (one side in the thickness direction), and the lower side on the paper is the lower side (the other side in the thickness direction).

[0029] like Figure 1 A and Figure 3 As shown in A of FIG. 1 , a sealing sheet 1 according to one embodiment of the present invention is an electronic component sealing sheet for sealing an electronic component 51 in an electronic member including a substrate 50 and an electronic component 51 .

[0030] The sealing sheet 1 is a component for manufacturing the electronic component package 7 described later, and is not the electronic component package 7 itself. The sealing sheet 1 does not contain the electronic component 51 and the substrate 50 on which the electronic component 51 is mounted. Specifically, the sealing sheet 1 is a member distributed as a component itself and is industrially usable.

[0031] It should be noted that the sealing sheet 1 is not the sealing sheet 8 ( Figure 3 B and Figure 3 C), that is, the sheet before the electronic component 51 is sealed.

[0032] like Figure 1 As shown in A in FIG. 1 , the sealing sheet 1 has a substantially plate shape (film shape) extending in a direction (surface direction) perpendicular to the thickness direction.

[0033] The sealing sheet 1 includes the first layer 2 and the second layer 3 in this order toward the upper side. That is, the sealing sheet 1 includes the first layer 2 and the second layer 3 disposed on the upper surface of the first layer 2. The sealing sheet 1 is preferably formed of only the first layer 2 and the second layer 3.

[0034] The first layer 2 is a lower layer that forms the lower surface (the surface on the other side in the thickness direction) of the sealing sheet 1. The first layer 2 has a substantially plate shape extending in the surface direction. The first layer 2 is described later and is a layer that is formed on the sealing sheet 1 to be provided to the electronic component 51 (see Figure 3 A) A contact layer that contacts the electronic component 51 when sealing.

[0035] The material of the first layer 2 is, for example, a first composition containing a first organic component and a first inorganic filler.

[0036] The first organic component contains a first thermosetting resin and a first thermoplastic resin.

[0037] The first thermosetting resin is a resin that is temporarily softened by heating when the electronic element 51 is sealed, is melted and flows, and is cured by further heating.

[0038] In addition, the first thermosetting resin is in the B stage in the first layer 2 before the electronic element 51 is sealed, and is not in the C stage (that is, in a state before being completely cured).

[0039] As the first thermosetting resin, for example, epoxy resin, phenolic resin, melamine resin, vinyl ester resin, cyanoester resin, maleimide resin, silicone resin, etc. can be listed. These first thermosetting resins can be used alone or in combination of two or more. As the first thermosetting resin, from the viewpoint of heat resistance, etc., preferably epoxy resin and phenolic resin can be listed, and more preferably a combination of epoxy resin and phenolic resin can be listed.

[0040] As epoxy resin, bifunctional epoxy resins such as bisphenol A type epoxy resin, bisphenol F type epoxy resin, modified bisphenol A type epoxy resin, modified bisphenol F type epoxy resin, biphenyl type epoxy resin, for example, phenol novolac type epoxy resin, cresol novolac type epoxy resin, trihydroxyphenylmethane type epoxy resin, tetrahydroxyphenylethane type epoxy resin, dicyclopentadiene type epoxy resin, etc. can be listed. These epoxy resins can be used alone or in combination of two or more. Preferably, bifunctional epoxy resins can be listed, and more preferably, bisphenol F type epoxy resin can be listed.

[0041] The epoxy equivalent of the epoxy resin is, for example, 230 g / eq. or less, preferably 210 g / eq. or less, and, for example, 10 g / eq. or more, preferably 50 g / eq. or more.

[0042] The softening point of the epoxy resin is, for example, 50° C. or higher, preferably 70° C. or higher, and, for example, 110° C. or lower, preferably 90° C. or lower.

[0043] The ratio of the epoxy resin to the first thermosetting resin is, for example, 40 mass % or more, preferably 60 mass % or more, and, for example, 90 mass % or less, preferably 70 mass % or less.

[0044] Phenolic resin is a resin that cures together with epoxy resin. As phenolic resin, for example, polyfunctional phenolic resins having more than three functions such as phenol novolac resin, cresol novolac resin, phenol aralkyl resin, phenol biphenyl resin, dicyclopentadiene type phenolic resin, and resol phenolic resin can be listed. These phenolic resins can be used alone or in combination of two or more. Preferably, phenol novolac resin can be listed.

[0045] The hydroxyl equivalent of the phenol resin is, for example, 230 g / eq. or less, preferably 210 g / eq. or less, and, for example, 10 g / eq. or more, preferably 50 g / eq. or more.

[0046] The softening point of the phenol resin is, for example, 40° C. or higher, preferably 50° C. or higher, and, for example, 90° C. or lower, preferably 70° C. or lower.

[0047] The ratio of the phenol resin to the first thermosetting resin is, for example, 10 mass % or more, preferably 30 mass % or more, and, for example, 60 mass % or less, preferably 40 mass % or less.

[0048] The ratio of the epoxy resin to the phenol resin is adjusted so that the total amount of hydroxyl groups in the phenol resin is, for example, 0.7 to 1.5 equivalents, preferably 0.9 to 1.2 equivalents, per 1 equivalent of epoxy groups in the epoxy resin.

[0049] The proportion of the first thermosetting resin relative to the first organic component is, for example, 10% by mass or more, preferably 20% by mass or more, and, for example, 50% by mass or less, preferably 40% by mass or less. The proportion of the first thermosetting resin relative to the first composition is, for example, 1% by mass or more, preferably 2% by mass or more, and, for example, 10% by mass or less, preferably 5% by mass or less.

[0050] The first thermoplastic resin is a resin that softens when heated, but is a resin that does not cure by heat.

[0051] Examples of the first thermoplastic resin include natural rubber, butyl rubber, isoprene rubber, chloroprene rubber, ethylene-vinyl acetate copolymer, ethylene-acrylic acid copolymer, ethylene-acrylate copolymer, polybutadiene resin, polycarbonate resin, thermoplastic polyimide resin, polyamide resin (6-nylon, 6,6-nylon, etc.), phenoxy resin, acrylic resin, saturated polyester resin (PET, etc.), polyamide-imide resin, fluororesin, styrene-isobutylene-styrene block copolymer, etc. Preferably, an acrylic resin is used.

[0052] Examples of acrylic resins include acrylic polymers obtained by polymerizing one or more (meth)acrylic acid alkyl esters having a linear or branched alkyl group as monomer components. It should be noted that "(meth)acrylic acid" means "acrylic acid and / or methacrylic acid".

[0053] Examples of the alkyl group include alkyl groups having 1 to 20 carbon atoms, such as methyl, ethyl, propyl, isopropyl, n-butyl, tert-butyl, isobutyl, pentyl, isopentyl, hexyl, heptyl, cyclohexyl, 2-ethylhexyl, octyl, isooctyl, nonyl, isononyl, decyl, isodecyl, undecyl, lauryl, tridecyl, tetradecyl, stearyl, octadecyl, and dodecyl. Preferably, an alkyl group having 1 to 6 carbon atoms is used.

[0054] The acrylic polymer may be a copolymer of an alkyl (meth)acrylate and other monomers (copolymerizable monomers).

[0055] Examples of other monomers (copolymerizable monomers) include glycidyl group-containing monomers such as glycidyl acrylate and glycidyl methacrylate, carboxyl group-containing monomers such as acrylic acid, methacrylic acid, carboxyethyl acrylate, carboxypentyl acrylate, itaconic acid, maleic acid, fumaric acid, and crotonic acid, acid anhydride monomers such as maleic anhydride and itaconic anhydride, 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, and 1,1-dihydroxybutyl (meth)acrylate. Hydroxyl-containing monomers such as 8-hydroxyoctyl acrylate, 10-hydroxydecyl (meth)acrylate, 12-hydroxylauryl (meth)acrylate or (4-hydroxymethylcyclohexyl)-methyl acrylate, such as styrenesulfonic acid, allylsulfonic acid, 2-(meth)acrylamide-2-methylpropanesulfonic acid, (meth)acrylamidepropanesulfonic acid, (meth)acryloxynaphthalenesulfonic acid, such as sulfonic acid monomers, such as 2-hydroxyethylacryloyl phosphate, such as styrene monomers, such as acrylonitrile. These monomers can be used alone or in combination of two or more. Among these, preferably carboxyl-containing monomers can be listed.

[0056] The glass transition temperature (Tg) of the first thermoplastic resin is, for example, 30° C. or less, preferably 0° C. or less, more preferably -5° C. or less, and, for example, -50° C. or more. When Tg is below the upper limit, the sealing sheet 1 easily penetrates into the gaps between the plurality of electronic components 51 during sealing, and the embedding property is further improved.

[0057] The glass transition temperature was obtained from the maximum value of the loss tangent (tan δ) measured by a dynamic viscoelasticity measuring apparatus (DMA, frequency 1 Hz, heating rate 10° C. / min).

[0058] The weight average molecular weight of the first thermoplastic resin is, for example, 100,000 or more, preferably 300,000 or more, and for example, 1,000,000 or less. The weight average molecular weight is measured by gel permeation chromatography (GPC) based on a standard polystyrene conversion value.

[0059] The proportion of the first thermoplastic resin relative to the first organic component is, for example, 40 mass % or more, preferably 50 mass % or more, more preferably 55 mass % or more, and, for example, 90 mass % or less, preferably 80 mass % or less, more preferably 65 mass % or less.

[0060] The ratio of the first thermoplastic resin to the first composition is, for example, 1 mass % or more, preferably 5 mass % or more, and, for example, 30 mass % or less, preferably 20 mass % or less.

[0061] The first organic component may contain other organic components such as the first silane coupling agent in addition to the first thermosetting resin and the first thermoplastic resin. Preferably, the first organic component contains the first silane coupling agent. Thus, the silane coupling agent improves the affinity between the resin and the filler, so that the dispersion stability becomes good when the filler is highly filled.

[0062] Examples of the first silane coupling agent include vinyl-containing silane coupling agents, epoxy-containing silane coupling agents, styrene-containing silane coupling agents, (meth)acrylic-containing silane coupling agents, amino-containing silane coupling agents, isocyanurate-containing silane coupling agents, and mercapto-containing silane coupling agents. Preferably, epoxy-containing silane coupling agents are used.

[0063] Examples of the epoxy group-containing silane coupling agent include 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, 3-glycidoxypropylmethyldimethoxysilane, 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropylmethyldiethoxysilane, and 3-glycidoxypropyltriethoxysilane. From the viewpoint of reactivity, preferably, 3-glycidoxypropyltriethoxysilane is used.

[0064] The proportion of the first silane coupling agent relative to the first organic component is, for example, 1% by mass or more, preferably 5% by mass or more, and, for example, 20% by mass or less, preferably 10% by mass or less. The proportion of the first silane coupling agent relative to the first composition is, for example, 0.1% by mass or more, preferably 0.5% by mass or more, and, for example, 5% by mass or less, preferably 3% by mass or less.

[0065] The ratio of the first organic component to the first composition is, for example, 5 mass % or more, preferably 10 mass % or more, and, for example, 50 mass % or less, preferably 35 mass % or less, and more preferably 20 mass % or less.

[0066] As the first inorganic filling material, for example, quartz glass, talc, silicon dioxide (fused silica, crystalline silica, etc.), aluminum oxide, aluminum nitride, silicon nitride, boron nitride, etc. can be listed. These inorganic filling materials can be used alone or in combination of two or more. As the inorganic filling material, preferably silicon dioxide and aluminum oxide can be listed, and more preferably silicon dioxide can be listed.

[0067] The size of the first inorganic filler is not particularly limited. Specifically, the average particle size is, for example, 0.1 μm or more, preferably 0.2 μm or more, and, for example, 20 μm or less, preferably 15 μm or less. In addition, two or more inorganic fillers having different average particle sizes can be used in combination. Such inorganic fillers are described in, for example, Japanese Patent Publication No. 2016-162909.

[0068] The ratio of the first inorganic filler to the first composition is, for example, 50% by mass or more, preferably 65% ​​by mass or more, more preferably 80% by mass or more, and, for example, 95% by mass or less, preferably 90% by mass or less. When the ratio of the first inorganic filler is within the above range, the heat-resistant reliability of the electronic component package 7 (described later) is further excellent.

[0069] Furthermore, the first composition may contain a curing accelerator and a pigment.

[0070] Curing accelerator is a catalyst (thermosetting catalyst) that promotes the curing of thermosetting resin by heating. As curing accelerator, imidazole compounds such as 2-phenyl-4,5-dihydroxydimethylimidazole (2PHZ-PW), 2-phenyl-4-methyl-5-hydroxymethylimidazole (2P4MHZ), such as organic phosphorus compounds, etc. can be listed. Preferably, imidazole compounds can be listed. In addition, inclusion compounds with the above-mentioned imidazole compounds as guests and hydroxyisophthalic acid (HIPA) as the main body can also be listed. It should be noted that inclusion compounds are, for example, recorded in Japanese Patent Publication No. 2012-232994. These curing accelerators can be used alone or in combination of two or more.

[0071] The ratio of the curing accelerator is, for example, 0.1 parts by mass or more, and for example, 5 parts by mass or less, relative to 100 parts by mass of the first thermosetting resin.

[0072] Examples of the pigment include black pigments such as carbon black. The average particle size of the pigment is, for example, 0.001 μm or more and 1 μm or less. These pigments may be used alone or in combination of two or more.

[0073] The ratio of the pigment to the first composition is, for example, 0.1 mass % or more, and, for example, 5 mass % or less.

[0074] Furthermore, the first composition may contain additives other than the above-mentioned components at appropriate ratios.

[0075] The thickness T1 of the first layer 2 is, for example, 10 μm or more, or preferably 50 μm or more, and, for example, 100 μm or less, or preferably 80 μm or less.

[0076] The second layer 3 is an upper layer that forms the upper surface (the surface on one side in the thickness direction) of the sealing sheet 1. The second layer 3 has a roughly plate shape extending in the surface direction. The second layer 3 is arranged on the entire upper surface of the first layer 2. The second layer 3 is described later, and is an exposed layer exposed to the outside (upper side) when the electronic component 51 is sealed by the sealing sheet 1. It should be noted that the second layer 3 is preferably a non-contact layer that does not contact the electronic component 51.

[0077] The material of the second layer 3 is a second composition containing a second organic component and a second inorganic filler.

[0078] The second organic component contains a second thermosetting resin, and preferably contains a second thermosetting resin and a second thermoplastic resin.

[0079] Examples of the second thermosetting resin include the same thermosetting resins as those exemplified in the first thermosetting resin. Preferred examples of the second thermosetting resin include epoxy resins and phenolic resins, and specifically, a combination of epoxy resins and phenolic resins may be used.

[0080] The ratio of the epoxy resin to the second thermosetting resin is, for example, 40 mass % or more, preferably 60 mass % or more, and, for example, 90 mass % or less, preferably 70 mass % or less.

[0081] The ratio of the phenol resin to the second thermosetting resin is, for example, 10 mass % or more, preferably 30 mass % or more, and, for example, 60 mass % or less, preferably 40 mass % or less.

[0082] The ratio of the epoxy resin to the phenol resin is adjusted so that the total amount of hydroxyl groups in the phenol resin is, for example, 0.7 to 1.5 equivalents, preferably 0.9 to 1.2 equivalents, per 1 equivalent of epoxy groups in the epoxy resin.

[0083] The proportion of the second thermosetting resin relative to the second organic component is, for example, 60% by mass or more, preferably 70% by mass or more, and, for example, 100% by mass or less, preferably 95% by mass or less, and more preferably 90% by mass or less. The proportion of the second thermosetting resin relative to the second composition is, for example, 5% by mass or more, preferably 10% by mass or more, and, for example, 25% by mass or less, preferably 15% by mass or less.

[0084] Examples of the second thermoplastic resin include the same thermoplastic resins as those exemplified for the first thermoplastic resin, and preferably, an acrylic resin is used.

[0085] The proportion of the second thermoplastic resin relative to the second organic component is, for example, 0% by mass or more, preferably 1% by mass or more, more preferably 5% by mass or more, and, for example, 40% by mass or less, preferably 30% by mass or less, more preferably 20% by mass or less. The proportion of the second thermoplastic resin relative to the second composition is, for example, 0.1% by mass or more, preferably 0.5% by mass or more, and, for example, 10% by mass or less, preferably 5% by mass or less.

[0086] The mass ratio A2 of the second thermoplastic resin to the second organic component is preferably smaller than the mass ratio A1 of the first thermoplastic resin to the first organic component. Specifically, the difference in their mass ratios (A1-A2) is, for example, 5% by mass or more, preferably 10% by mass or more, more preferably 25% by mass or more, and, for example, 60% by mass or less, preferably 50% by mass or less. When the difference is within the above range, the upper surface of the second layer 3 can be made softer than the lower surface of the first layer 2 more reliably.

[0087] The second organic component may contain other organic components such as a second silane coupling agent in addition to the second thermosetting resin and the second thermoplastic resin. Preferably, the second organic component contains a second silane coupling agent. Thus, the silane coupling agent improves the affinity between the resin and the filler, and thus the dispersion stability becomes good when the filler is highly filled.

[0088] Examples of the second silane coupling agent include the same silane coupling agents as those exemplified for the first silane coupling agent. Preferably, an epoxy group-containing silane coupling agent is used.

[0089] The proportion of the second silane coupling agent relative to the second organic component is, for example, 1% by mass or more, preferably 5% by mass or more, and, for example, 20% by mass or less, preferably 10% by mass or less. The proportion of the second silane coupling agent relative to the second composition is, for example, 0.1% by mass or more, preferably 0.5% by mass or more, and, for example, 5% by mass or less, preferably 3% by mass or less.

[0090] The ratio of the second organic component to the second composition is, for example, 5 mass % or more, preferably 10 mass % or more, and, for example, 50 mass % or less, preferably 35 mass % or less, and more preferably 20 mass % or less.

[0091] Examples of the second inorganic filler include the same inorganic fillers as those exemplified in the first inorganic filler, and preferably, silicon dioxide is used.

[0092] The proportion of the second inorganic filler relative to the second composition is, for example, 50% by mass or more, preferably 65% ​​by mass or more, more preferably 80% by mass or more, and, for example, 95% by mass or less, preferably 90% by mass or less. When the proportion of the second inorganic filler is within the above range, the heat-resistant reliability of the electronic component package 7 (described later) is excellent.

[0093] In addition, the ratio [C2 / C1] of the ratio C2 (mass %) of the second inorganic filler relative to the second composition to the ratio C1 (mass %) of the first inorganic filler relative to the first composition is, for example, 0.5 or more, preferably 0.8 or more, and, for example, 2.0 or less, preferably 1.3 or less. When the above ratio is within the above range, cracks at the interface between the first layer 2 and the second layer 3 can be suppressed for the electronic component package 7 (described later).

[0094] The second composition may contain the curing accelerator, pigment, and the like exemplified in the first composition at an appropriate ratio.

[0095] The thickness T2 of the second layer 3 is, for example, 100 μm or more, preferably 130 μm or more, more preferably 150 μm or more, and is, for example, 1000 μm or less, preferably 500 μm or less, more preferably 300 μm or less.

[0096] The ratio of the thickness T2 of the second layer 3 to the thickness T1 of the first layer 2 satisfies the formula (1), and preferably satisfies the formula (2).

[0097] 1.5 <T2 / T1<5 (1)

[0098] 1.8≤T2 / T1≤4.5 (2)

[0099] By satisfying the above formula, it is possible to take into account both the low contamination during sealing and the heat resistance reliability after sealing.

[0100] In the sealing sheet 1, the upper surface of the second layer 3 is softer than the lower surface of the first layer 2 at 90°C. That is, the lower surface (the other surface in the thickness direction) of the first layer 2 is harder than the upper surface (one surface in the thickness direction) of the second layer 3 at 90°C. In other words, the upper surface of the second layer 3 is more likely to be indented than the lower surface of the first layer 2 at 90°C.

[0101] Specifically, as Figure 2 shown in the iron ball drop test of A, the sealing sheet 1 is arranged on the heating table 10 with the first layer 2 on the upper side, and the sealing sheet 1 is heated to 90°C. Then, the iron ball 11 is dropped onto the surface (lower surface) of the first layer 2. At this time, as Figure 2 shown in B, the amount of indentation (depth) formed on the surface of the first layer 2 is set as D1. In addition, similarly, the sealing sheet 1 is arranged on the heating table 10 with the second layer 3 on the upper side, and the sealing sheet 1 is heated to 90°C. Then, the iron ball 11 is dropped onto the surface (upper surface) of the second layer 3. At this time, the amount of indentation (depth) formed on the surface of the second layer 3 is set as D2. In this case, the amount of indentation D2 of the second layer 3 is larger than the amount of indentation D1 of the first layer 2. That is, D1 < D2 is satisfied.

[0102] Specifically, the amount of indentation D1 in the iron ball drop test is, for example, less than 20 μm, preferably 15 μm or less, and, for example, 5 μm or more, preferably 10 μm or more.

[0103] The amount of indentation D2 in the iron ball drop test is, for example, 20 μm or more, preferably 25 μm or more, and, for example, 100 μm or less, preferably 40 μm or less.

[0104] Regarding the size of the iron ball, the diameter is 18 mm, the weight is 10 g, and the drop height is 10 cm. Specifically, it will be described in the examples.

[0105] When the second layer 3 is softer than the first layer 2 at 90°C, it is possible to achieve good embedability, low contamination during sealing, and heat resistance reliability after sealing.

[0106] In the sealing sheet 1, it is preferable to satisfy 0.1 < D2 / T2 < 0.2, and more preferably to satisfy 0.15 ≤ D2 / T2 ≤ 0.19. When the above ratio is within the above range, it is possible to more reliably take into account both low contamination and embedability.

[0107] When manufacturing the sealing sheet 1, as Figure 1 shown in B of, the first layer 2 and the second layer 3 are prepared separately.

[0108] For example, the first composition is dissolved and / or dispersed in a solvent (e.g., methyl ethyl ketone, toluene, ethyl acetate, etc.) to prepare a first varnish, which is applied to the first release sheet 4 shown by the virtual line and dried.

[0109] The second composition is dissolved and / or dispersed in a solvent to prepare a second varnish, which is applied to the second release sheet 5 indicated by a virtual line and dried. Thus, the second layer 3 is prepared in a state supported by the second release sheet 5 .

[0110] Alternatively, the first layer 2 and / or the second layer 3 may be prepared by kneading and extrusion without preparing a varnish.

[0111] The first thermosetting resin in the first layer 2 and the second thermosetting resin in the second layer 3 are in a B-stage state, for example.

[0112] Then, the first layer 2 and the second layer 3 are bonded together.

[0113] Next, refer to Figure 3 AC, a method for manufacturing an electronic component package 7 by sealing an electronic component 51 using the sealing sheet 1 will be described. It should be noted that the electronic component 51, the electronic component package 7 and the manufacturing method thereof are also described in Japanese Patent Application Laid-Open No. 2016-162909.

[0114] like Figure 3 As shown in A, first, the electronic component 51 is prepared.

[0115] The electronic component 51 has a generally flat plate shape extending in the surface direction. The electronic component 51 is not particularly limited, and various electronic components can be listed, for example, hollow electronic components, semiconductor components, etc. A plurality of electronic components 51 are installed in a manner opposite to the upper surface of the substrate 50. For example, the plurality of electronic components 51 are flip-chip mounted relative to the substrate 50. In this case, electrodes (not shown) provided on the lower surfaces of the plurality of electronic components 51 are electrically connected to terminals (not shown) provided on the upper surface of the substrate 50. In addition, chip bonding can also be performed relative to the electronic component 51 with the aid of an adhesive layer (chip bonding film, etc.) not shown in the figure.

[0116] In order to prepare the electronic component 51 , an electronic component mounting substrate 55 including the electronic component 51 and the substrate 50 on which the electronic component 51 is mounted is prepared.

[0117] The substrate 50 is, for example, a printed circuit board. The substrate 50 has a substantially flat plate shape extending in the plane direction. The substrate 50 has a size that surrounds a plurality of electronic components 51 when viewed from above. The substrate 50 has terminals (not shown) electrically connected to the electronic components 51 on its upper surface. The substrate 50 is, for example, made of a ceramic plate, a glass epoxy plate, or the like.

[0118] Next, the sealing sheet 1 is prepared.

[0119] The size of the sealing sheet 1 is adjusted to a size capable of sealing the plurality of electronic components 51 collectively, that is, to have a size that includes all of the plurality of electronic components 51 when projected in the thickness direction.

[0120] like Figure 3 As shown in B, the electronic element 51 is then sealed with the sealing sheet 1 .

[0121] For example, using Figure 3 A flat plate pressing machine 97 including a lower plate 98 and an upper plate 99 indicated by a virtual line B seals the electronic component 51 with the sealing sheet 1 .

[0122] The electronic component mounted substrate 55 is disposed on the lower plate 98 . Specifically, the lower surface of the substrate 50 is placed on the upper surface of the lower plate 98 .

[0123] Next, the sealing sheet 1 is placed on the electronic component mounting substrate 55. Specifically, the first layer 2 is brought into contact with the upper surface of the plurality of electronic components 51. On the other hand, the second layer 3 faces upward. At this time, the first peeling sheet 4 is peeled off from the first layer 2 while supporting the first peeling sheet 4.

[0124] Next, the upper plate 99 is pressed down toward the sealing sheet 1. At the same time, the sealing sheet 1 is heated by a heat source (not shown) provided on the lower plate 98 and the upper plate 99.

[0125] The heating temperature is, for example, 40° C. or more, preferably 60° C. or more, and, for example, 100° C. or less, preferably 95° C. or less. The pressure is, for example, 0.05 MPa or more, preferably 0.1 MPa or more, and, for example, 10 MPa or less, preferably 5 MPa or less. The pressing time is, for example, 0.3 minute or more, preferably 0.5 minute or more, and, for example, 10 minutes or less, preferably 5 minutes or less.

[0126] It should be noted that, in the hot pressing, in addition to the flat press 97 ( Figure 3 In addition to the virtual line B), a roller press or the like may also be used.

[0127] When the sealing sheet 1 is heat-pressed, the sealing sheet 1 softens and simultaneously buries the plurality of electronic components 51. In other words, the plurality of electronic components 51 are buried in the sealing sheet 1.

[0128] Specifically, the first layer 2 covers the upper surface and side surfaces of the electronic element 51 and the upper surface of the substrate 50 that does not overlap with the electronic element 51 when projected in the thickness direction. That is, the first layer 2 plastically deforms in accordance with the outer shape of the electronic element 51.

[0129] On the other hand, the lower surface of the second layer 3 is deformed in accordance with the deformation of the first layer 2 , but the upper surface of the second layer 3 is pressed by the upper plate 99 , and thus maintains a flat shape.

[0130] At this time, the second layer 3 is relatively soft, so it presses the first layer 2 to the lower side. Therefore, the first layer 2 also flows (immerses) between the multiple electronic components 51, such as the corner formed by the side surface of the electronic component 1 and the upper surface of the substrate 50, and buries them without gaps.

[0131] On the other hand, since the first layer 2 is relatively hard, it will not excessively wet and spread on the substrate 50, and will not easily flow to the outside of the substrate 50, that is, the lower plate 98. Therefore, the first layer 2 will not easily reach the lower plate 98, the side or lower surface of the substrate 50, and the surrounding contamination can be suppressed.

[0132] Then, the sealing sheet 1 is cured by heating. Specifically, the first thermosetting resin contained in the first layer 2 and the second thermosetting resin contained in the second layer 3 are thermally cured (completely cured, brought to a C-stage).

[0133] After sealing and curing, the sheet that seals the electronic element 51 is no longer the sealing sheet 1 but the sealing sheet 8. The sealing sheet 8 is not in a flat plate shape, but has a concave portion that opens downward corresponding to the electronic element 51.

[0134] In the sealing sheet 8 , the first thermosetting resin and the second thermosetting resin are in the C stage.

[0135] Before the sealing sheet 1 is thermally cured, the second release sheet 5 is peeled from the second layer 3 while supporting the second layer 3. Alternatively, the second release sheet 5 may be peeled from the second layer 3 before the electronic element 51 is sealed with the sealing sheet 1.

[0136] The heating temperature (curing temperature) is, for example, 100° C. or more, preferably 120° C. or more, and for example, 200° C. or less, preferably 180° C. or less. The heating time is, for example, 10 minutes or more, preferably 30 minutes or more, and for example, 180 minutes or less, preferably 120 minutes or less.

[0137] When the sealing sheet 1 is thermally cured, the sealing sheet 1, the electronic component 51, and the substrate 50 are taken out of the flat press 97 and placed in, for example, a heating furnace. It should be noted that the sealing sheet 1, the electronic component 51, and the substrate 50 may be thermally cured using a heat source provided in the flat press 97 without taking the sealing sheet 1, the electronic component 51, and the substrate 50 out of the flat press 97.

[0138] If necessary, the upper surface of the second layer 3 located on the plurality of electronic components 51 is then marked (labeled) by laser irradiation or the like. The label includes information related to the electronic component package 7 (product information, lot number, etc.) described below.

[0139] like Figure 3 As shown in C, the sealing sheet 8 between the plurality of electronic components 51 is then cut by, for example, dicing to separate the electronic components 51 and the substrate 50. Thus, an electronic component package 7 including one sealing sheet 8, one electronic component 51, and one substrate 50 is manufactured.

[0140] Then, the electronic component package 7 is mounted on another substrate.

[0141] Moreover, for Figure 1 In the sealing sheet 1 (sheet before the sealing sheet 8 is formed) shown in A, the upper surface of the second layer 3 is softer than the lower surface of the first layer 2 at 90° C. The ratio of the thickness T2 of the second layer 3 to the thickness T1 of the first layer 2 satisfies 1.5 <T2 / T1<5。

[0142] Therefore, when the sealing sheet 1 is heated to seal the electronic component 1, the second layer 3 having a sufficient thickness can press the first layer 2 to the lower side. Therefore, the first layer 2 also flows between the plurality of electronic components 51, for example, the corner formed by the side surface of the electronic component 1 and the upper surface of the substrate 50, and buries them without gaps. That is, the embedding property is excellent. Therefore, it is possible to suppress the generation of unnecessary gaps in the obtained electronic component package 7.

[0143] In addition, during sealing, the hard first layer 2 is in contact with the electronic component 51 and the substrate 50, so it becomes difficult to wet and spread. On the other hand, since the thickness of the soft second layer 3 is within a specified range, the amount of the second layer 3 that is easy to wet and spread is reduced. Therefore, the protrusion of the sealing sheet 1 can be suppressed. Therefore, the contamination around the electronic component package 7 can be suppressed.

[0144] On the other hand, after sealing, the relatively soft second layer 3 is sufficiently present outside the electronic component package 7 compared with the relatively hard first layer 2, so cracks are less likely to occur due to expansion / contraction caused by thermal cycles, and the heat-resistant reliability is excellent.

[0145] In addition, in the sealing sheet 1, when the ratio of the recess amount D2 to the thickness T2 of the second layer 3 satisfies 0.1 < D2 / T2 < 0.2, low contamination and embeddability can be more reliably achieved simultaneously.

[0146] In addition, when the ratio of the second thermoplastic resin to the second organic component is smaller than the ratio of the first thermoplastic resin to the first organic component, the physical properties of the sealing sheet 1 can be easily adjusted.

[0147] Examples

[0148] Examples and comparative examples are shown below to more specifically illustrate the present invention. It should be noted that the present invention is not limited by any of the examples and comparative examples. In addition, the specific numerical values such as the compounding ratio (content ratio), physical property values, parameters, etc. used in the following description can be replaced with the corresponding compounding ratio (content ratio), physical property values, parameters, etc. described in the above "Detailed Description", which are the upper limits (values defined as "below" and "less than") or lower limits (values defined as "above" and "exceeding") of those.

[0149] The respective components used in the examples and comparative examples are shown below.

[0150] YSLV-80XY: Epoxy resin (bisphenol F type epoxy resin), epoxy equivalent: 200 g / eq., softening point: 80 °C, manufactured by Nippon Steel Chemical Co., Ltd.

[0151] LVR8210DL: Phenolic resin (novolak type phenolic resin), hydroxyl equivalent: 104 g / eq., softening point: 60 °C, manufactured by Gun Ei Chemical Industry Co., Ltd.

[0152] HME-2006M: Acrylic resin (methyl ethyl ketone solution containing 20% by mass of a carboxyl group-containing acrylate polymer, weight average molecular weight: about 600,000, Tg: -30 °C, manufactured by Negami Sangyo Co., Ltd.

[0153] SG-70L: Acrylic resin (methyl ethyl ketone solution containing 12.5% by mass of a carboxyl group-containing acrylate polymer, weight average molecular weight: about 800,000, Tg: -10 °C, manufactured by Nagase ChemteX Corporation

[0154] KBM-403: Epoxysilane coupling agent, 3-glycidoxypropyltrimethoxysilane, manufactured by Shin-Etsu Silicones Co., Ltd.

[0155] FB-8SM: Silicon dioxide, average particle size: 6 μm, manufactured by Denka Company Limited

[0156] SC220G-SMJ: Silica, average particle size: 0.5 μm, manufactured by ADMATECHS CO., LTD.

[0157] #20: Carbon black, average particle size: 50 nm, manufactured by Mitsubishi Chemical Corporation

[0158] 2PHZ-PW: Curing accelerator, imidazole compound (2-phenyl-4,5-dihydroxydimethylimidazole), manufactured by Shikoku Chemicals Co., Ltd.

[0159] Example 1

[0160] According to the compounding formula described in Table 1 (the numerical values ​​in Table 1 represent the solid content), each component was dissolved and dispersed in methyl ethyl ketone to obtain a first varnish and a second varnish. The solid content concentration of the first varnish was 70% by mass, and the solid content concentration of the second varnish was 80% by mass.

[0161] The first varnish and the second varnish were applied to the surfaces of the first release sheet 4 and the second release sheet 5, respectively, and then dried at 110° C. for 5 minutes. Thus, the first layer 2 with a thickness of 50 μm and the second layer 3 with a thickness of 200 μm were prepared.

[0162] Then, the first layer 2 and the second layer 3 are bonded together. Thus, the sealing sheet 1 including the first layer 2 (lower layer) and the second layer 3 (upper layer) is produced.

[0163] Examples 2 to 5 and Comparative Examples 1 to 8

[0164] According to the compounding recipes described in Tables 1 and 2 and the thickness described in Table 3, the same procedure as in Example 1 was carried out to prepare a sealing sheet 1 .

[0165] (evaluate)

[0166] The following items were evaluated. The results are shown in Table 3.

[0167] <Measurement of the amount of depression>

[0168] Polyethylene terephthalate (38 μm thick) was placed on the upper and lower surfaces of the sealing sheet (50 mm × 50 mm) of each embodiment and each comparative example. Then, the sheet was placed on a hot plate 10 at 90°C with the first layer at the lower side and the second layer at the upper side. After 1 minute, an iron ball 11 (18 mm in diameter and 10 g in weight) was dropped from a height of 10 cm onto the upper surface of the sealing sheet. After dropping, the sheet was left standing for 5 minutes and the iron ball 11 was removed (see Figure 2 AB).

[0169] The amount of depression D2 of the upper surface (surface on the second layer side) of the sealing sheet was measured using a 3CCD color confocal microscope (manufactured by Lasertec Corporation, “MC-1000A”) in confocal mode at a magnification of 5 times.

[0170] The depression amount D1 of the surface on the first layer side was measured in the same manner as described above except that the first layer was arranged on the upper side and the second layer was arranged on the lower side.

[0171] Table 3 shows the results.

[0172] <Evaluation of low pollution properties>

[0173] A glass plate 20 of 100 mm×100 mm×1.1 mm thick was prepared. The sealing sheet 1 (80 mm×80 mm×260 μm thick) of each example and each comparative example was placed at the center of the glass plate 20 in contact with the first layer, and they were bonded together using a vacuum flat press at a pressure of 0.1 MPa, 65° C., and 1 minute.

[0174] Next, the lengths L1 and L2 of the straight lines connecting the midpoints of the two opposing sides of the bonded sealing sheet were measured respectively (refer to Figure 4 ). The larger value is set as A, and the protrusion ratio X is calculated by the following formula.

[0175] X[%]=(A[mm] / 80[mm])×100

[0176] The case where X was 100% or more and 110% or less was evaluated as ○, the case where X exceeded 110% and was 120% or less was evaluated as △, and the case where X exceeded 120% was evaluated as ×.

[0177] <Evaluation of embedding properties>

[0178] A plurality of silicon chips (1 mm×1 mm×200 μm thick) were arranged in a grid pattern with a chip interval of 500 μm, and a sealing sheet was bonded thereto with the first layer in contact using a vacuum flat plate press at a pressure of 0.1 MPa, 65° C., and 1 minute.

[0179] At this time, the case where no gap was observed between the chips was evaluated as ○, the case where a gap of less than 100 μm was observed but no gap of 100 μm or more was observed was evaluated as △, and the case where a gap of 100 μm or more was observed was evaluated as ×. The results are shown in Table 3.

[0180] <Evaluation of Heat Resistance Reliability>

[0181] As a ceramic plate, an alumina plate of 100 mm × 100 mm × 200 μm thick was prepared. The sealing sheet (3 mm in diameter) of each embodiment and each comparative example was placed in the center of the ceramic plate in a first layer contact manner, and they were bonded together using a vacuum flat plate press at a pressure of 0.3 MPa, 95° C., and 50 seconds, and then heated and cured at 150° C. for 1 hour. Thus, a sample was obtained.

[0182] Next, the sample was subjected to a thermal cycle test (temperature of one cycle was -50°C to 125°C, 1 hour; 1000 cycles).

[0183] Then, the sample was observed using an ultrasonic microscope (SAT), and the case where no crack or peeling was observed in the sealing sheet was evaluated as ○, and the case where crack or peeling was observed was evaluated as ×. Table 3 shows the results.

[0184] [Table 1]

[0185]

[0186] [Table 2]

[0187]

[0188] [Table 3]

[0189]

Claims

1. A sealing sheet, characterized in that: It is a sealing sheet used to seal electronic components. The sealing sheet includes, in order toward one side in the thickness direction: a first layer in contact with the electronic component when the electronic component is sealed, and a second layer exposed to the outside. The first layer and the second layer are each thermosetting. One surface of the second layer in the thickness direction is softer than the other surface of the first layer in the thickness direction at 90° C., In an iron ball drop test at 90° C., the amount of depression formed on one surface of the second layer in the thickness direction is larger than the amount of depression formed on the other surface of the first layer in the thickness direction, wherein the diameter of the iron ball is 18 mm and the drop height is 10 cm. The ratio of the thickness T2 of the second layer to the thickness T1 of the first layer satisfies the following formula: 1.5 <T2 / T1<5, The ratio of the depression amount D2 formed on one surface of the second layer in the thickness direction in the iron ball drop test to the thickness T2 of the second layer satisfies the following formula: 0.1 <D2 / T2<0.2。